2012
DOI: 10.1111/apt.12131
|View full text |Cite
|
Sign up to set email alerts
|

An allergic phenotype and the use of steroid inhalers predict eosinophilic oesophagitis in patients with asthma

Abstract: SUMMARY BackgroundPatients with eosinophilic oesophagitis (EoE) commonly have asthma and atopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…It has already been postulated that the level of peripheral blood eosinophils holds promise as an EoE biomarker, although the incidences of peripheral blood eosinophilia in EoE patients (defined as 300/mm 3 ) might vary and be particularly influenced by confounders such as the role of seasons or concomitant atopic conditions . A significant correlation of blood eosinophilia with oesophageal eosinophil tissue infiltration has been reported in several studies and an increased blood eosinophil number has even been proposed as a predictive marker of EoE . However, so far only a few studies have systematically evaluated the value of blood eosinophils for monitoring treatment of EoE.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been postulated that the level of peripheral blood eosinophils holds promise as an EoE biomarker, although the incidences of peripheral blood eosinophilia in EoE patients (defined as 300/mm 3 ) might vary and be particularly influenced by confounders such as the role of seasons or concomitant atopic conditions . A significant correlation of blood eosinophilia with oesophageal eosinophil tissue infiltration has been reported in several studies and an increased blood eosinophil number has even been proposed as a predictive marker of EoE . However, so far only a few studies have systematically evaluated the value of blood eosinophils for monitoring treatment of EoE.…”
Section: Discussionmentioning
confidence: 99%
“…In a single adult study, use of corticosteroid inhalers for the treatment of asthma was reported as having a protective effect on the development of eosinophilic esophagitis. The authors acknowledged that this may not be a true protective effect but rather inadvertent treatment of eosinophilic esophagitis if inhalers are used incorrectly (swallowed instead of inhaled) . Therefore, when interpreting esophageal biopsies or improvement in symptoms in patients taking PPIs or inhaled steroids, it is critical to understand the impact these therapies may have on EoE and how they could interfere with making the correct diagnosis.…”
Section: Role Of Empiric Therapiesmentioning
confidence: 99%
“…Proposed algorithm for patients with refractory respiratory symptoms undergoing laryngoscopy or bronchoscopy RUBINSTEIN AND ROSEN | 1589 esophagitis if inhalers are used incorrectly (swallowed instead of inhaled) 29. Therefore, when interpreting esophageal biopsies or improvement in symptoms in patients taking PPIs or inhaled steroids, it is critical to understand the impact these therapies may have on EoE and how they could interfere with making the correct diagnosis.…”
mentioning
confidence: 99%
“…We also detected new pleural nerve connectivity to vessels and airways, derivation from airways, wrapping around from dorsal to ventral surfaces. Our method also found novel connections between the distal esophagus and inferior lungs via the mediastinal fascia that may relate to the association between airway disease (e.g., asthma and cough) and esophageal disease (e.g., eosinophilic esophagitis, reflux) (25)(26)(27)(28)(29)(30). The inability to image the whole lung and esophagus in prior studies likely led to undersampling, which explains differing conclusions about the distribution of visceral pleural nerves seen in these previous studies (23,24,31).…”
Section: Whole Lung Imaging Of Visceral Pleural Innervationmentioning
confidence: 99%